Overexpression of OsMYB48-1, a novel MYB-related transcription factor, enhances drought and salinity tolerance in rice - Xiong, Haiyan; Li, Jinjie; Liu, Pengli; Duan, Junzhi; Zhao, Yan; Guo, Xiao; Li, Yang; Zhang, Hongliang; Ali, Jauhar; Li, Zichao (Public Library of Science, 2014)
MYB-type transcription factors (TFs) play essential roles in plant growth, development and respond to environmental stresses. Role of MYB-related TFs of rice in drought stress tolerance is not well documented. Here, we report the isolation and characterization of a novel MYB-related TF, OsMYB48-1, of rice. Expression of OsMYB48-1 was strongly induced by polyethylene glycol (PEG), abscisic acid (ABA), H2O2, and dehydration, while being slightly induced by high salinity and cold treatment. The OsMYB48-1 protein was localized in the nucleus with transactivation activity at the C terminus. Overexpression of OsMYB48-1 in rice significantly improved tolerance to simulated drought and salinity stresses caused by mannitol, PEG, and NaCl, respectively, and drought stress was caused by drying the soil. In contrast to wild type plants, the overexpression lines exhibited reduced rate of water loss, lower malondialdehyde (MDA) content and higher proline content under stress conditions. Moreover, overexpression plants were hypersensitive to ABA at both germination and post-germination stages and accumulated more endogenous ABA under drought stress conditions. Further studies demonstrated that overexpression of OsMYB48-1 could regulate the expression of some ABA biosynthesis genes (OsNCED4, OsNCED5), early signaling genes (OsPP2C68, OSRK1) and late responsive genes (RAB21, OsLEA3, RAB16C and RAB16D) under drought stress conditions. Collectively, these results suggested that OsMYB48-1 functions as a novel MYB-related TF which plays a positive role in drought and salinity tolerance by regulating stress-induced ABA synthesis.